Poor Jurgis Rudkus: A Multi-theoretical Analysis of Socio-political Development in Upton Sinclair's The Jungle - Long, Alex (My University, 2015)
I argue that the legacy of Upton Sinclair's most famous novel, The Jungle, has wrongfully been obscured over time to resemble a literary canon version of Super Size Me and that there is contemporary significance to be gained if we revisit the text from a theoretically grounded, retrospective analysis. I organize my analysis by breaking the text into five distinct stages through which we can trace and observe the development of the protagonist, Jurgis Rudkus. With each stage, there is an accompanying concept or two from various social/critical theorists that is employed to enhance and complicate our reading and understanding of Sinclair's message. As the analysis of the novel progresses, I illustrate the methodical nature by which Sinclair explore various modes of being in a capitalist society, ultimately leading us to the conclusion that only through collective and resistive social action can the ills of capitalism begin to be alleviated.
Keywords: The Jungle (novel); American literature--20th century--History and criticism; Critical theory; Literary criticism